P229 A retrospective database study of persistence and adherence in patients with asthma in the UK (UK-THIN): fluticasone furoate/vilanterol (FF/VI) versus beclometasone dipropionate/formoterol (BDP/FM). (12th November 2019) - Svedsater, H; Parimi, M; Ann, Q; Gray, CM; Nixon, M; Boxall, N
Abstract : Introduction and objectives: A retrospective cohort analysis was conducted comparing persistence with, and adherence to, different inhaled corticosteroid/long-acting-β2 -agonist (ICS/LABA) treatments by asthma patients. Here we report findings from patients initiating treatment with either FF/VI or BDP/FM, the latter administered either as flexible or fixed-dose. Methods: Patients in the UK with data registered in The Health Improvement Network (THIN) database, who had a first prescription (index date) for any ICS/LABA between 1 January 2013–17 January 2018 (study period) and a prior asthma diagnosis, were included if they had ≥12 months medical history prior to index date plus ≥1 post-index ICS/LABA prescription. Patients were excluded if aged <18 years or if there were records for either COPD diagnosis or previous non–study ICS/LABA treatment prior to index date. Study cohorts were matched by propensity score (1:up to 4; greedy method). Primary objective was to compare persistence of comparator ICS/LABAs up to 12 months post-index treatment (time to discontinuation* including switch). Secondary objectives were: proportion of days covered (PDC) and proportion of patients with ≥50% and ≥80% PDC at 12 months post-index; and rescue use (annualised number of short-acting bronchodilator prescriptions/patient) within 12 months after treatment initiation. Results: A total of 894 patients initiating FF/VI were matched to 3433 patients initiating BDP/FM. A higher proportion of patients persisted with FF/VI versus BDP/FM over 12 months (Kaplan-Meier analysis; Figure ). The likelihood of discontinuing treatment within 12 months after initiation was 31% lower for FF/VI than BDP/FM (index year-adjusted, hazard ratio=0.69; 95% CI 0.60–0.80; p<0.001). Median (interquartile range) PDC was 89.2 (61.6–100.0) for FF/VI and 75.9 (50.5–98.0) for BDP/FM (p<0.0001), with significantly higher odds of achieving ≥50% and ≥80% PDC for FF/VI versus BDP/FM (747/893 [83.7%] vs 2600/3433 [75.7%]; odds ratio=1.50; 95% CI 1.23–1.83; p<0.001 and 526/893 [58.9%] vs 1571/3433 [45.8%]; odds ratio=1.57; 95% CI 1.35–1.83; p<0.001, respectively; per-protocol analyses). Annualised rescue use was numerically higher for FF/VI (9.0) versus BDP/FM (7.7). Conclusion: UK asthma patients initiating FF/VI were more likely to have higher persistence and better adherence to treatment than those initiating BDP/FM. GlaxoSmithKline plc. -funded study (209967/HO-18–19688).